2022
DOI: 10.1155/2022/3601545
|View full text |Cite|
|
Sign up to set email alerts
|

A Multimodal Model for College English Teaching Using Text and Image Feature Extraction

Abstract: The rapid development of the internet and multimedia technology in recent years has continued to push foreign language education in the direction of modern education. Multimodal education is becoming more and more important in the field of English education as an advanced educational concept in the field of language education. As a result, many English teachers have begun to emphasize the use of multimodal teaching theory in their classrooms. This paper investigates a multimodal model that incorporates text an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Finally, the exercises are inputted into the Attention-LSTM to generate multimodal exercise characterization vectors. This approach yields exercise representation vectors that encompass richer semantic information compared to unimodal exercise representation vectors and maximally capture the semantic characteristics embedded in the exercise resources [14][15][16]. As a result, it exhibits a significant improvement in performance on the "Finding Similar Exercises" task compared to the existing baseline at the time.…”
Section: Multimodal Characterization Methodsmentioning
confidence: 99%
“…Finally, the exercises are inputted into the Attention-LSTM to generate multimodal exercise characterization vectors. This approach yields exercise representation vectors that encompass richer semantic information compared to unimodal exercise representation vectors and maximally capture the semantic characteristics embedded in the exercise resources [14][15][16]. As a result, it exhibits a significant improvement in performance on the "Finding Similar Exercises" task compared to the existing baseline at the time.…”
Section: Multimodal Characterization Methodsmentioning
confidence: 99%
“…In the process of teaching, close integration between various modes and various types of network resources not only facilitates teaching and learning but also helps to improve students' professionalism and professionalism and provides a solid professional and linguistic foundation for students to participate in work or study abroad. In the process of teaching, the close integration of multiple modalities and various online resources not only facilitates the accuracy of information transmission but also plays an important role in the field of bilingual teaching [17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%